Pemanfaatan Media Wordwall pada Pembelajaran Keterampilan Menyimak Teks Biografi bagi Siswa Kelas X.5 SMA Negeri 3 Makassar - A. Alfahira Nur Annisa; Salam Salam; Hasriani Hasriani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Students' low motivation and listening skills in learning biographical texts have prompted the need for more interactive learning media. This study aims to describe the use of Wordwall media in teaching biographical text listening skills and its impact on the learning motivation of grade X.5 students at SMA Negeri 3 Makassar. This study used a descriptive qualitative approach with participatory observation as the primary data collection technique, supported by pre-tests and post-tests as supplementary data. The study subjects were 35 students. The results showed an increase in listening skills, as evidenced by a comparison of test results: in the pre-test, only 3 students scored 19-20, while in the post-test, this increased to 28 students, scoring 19-20. Observations showed that the majority of students fell into the